2017
DOI: 10.1186/s13049-017-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcomes and duration from cardiac arrest to the initiation of extracorporeal membrane oxygenation in patients with out-of-hospital cardiac arrest: a retrospective study

Abstract: BackgroundWe investigated the relationship between neurological outcomes and duration from cardiac arrest (CA) to the initiation of extracorporeal membrane oxygenation (ECMO) (CA-to-ECMO) in patients with out-of-hospital cardiac arrest (OHCA) treated with extracorporeal cardiopulmonary resuscitation (ECPR) and determined the ideal time at which ECPR should be performed.MethodsDuring the time period in which this study was conducted, 3451 patients experienced OHCA. This study finally included 79 patients aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 21 publications
2
57
4
4
Order By: Relevance
“…Several studies have sought to determine the factors associated with positive outcomes from ECPR, with varying results. While there is considerable prognostic factor heterogeneity between studies, a short ‘low flow time’, and an initial shockable rhythm, were most consistently associated with improved outcomes . Prehospital ECPR initiation potentially minimises this circulatory low flow time and has also been associated with significantly increased rates of ROSC .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have sought to determine the factors associated with positive outcomes from ECPR, with varying results. While there is considerable prognostic factor heterogeneity between studies, a short ‘low flow time’, and an initial shockable rhythm, were most consistently associated with improved outcomes . Prehospital ECPR initiation potentially minimises this circulatory low flow time and has also been associated with significantly increased rates of ROSC .…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 also included those who presented in asystole who then developed a shockable rhythm at the next rhythm check. While there is a paucity of literature concerning ECPR in patients with a shockable second rhythm, two studies identified that any ROSC event, or transient ROSC, before ECPR, predicted favourable outcomes. This was reflected in the inclusion of non‐sustained ROSC as an alternative second rhythm in Group 3 inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations